Highly Selective Two‐Electron Electrocatalytic CO2 Reduction on Single‐Atom Cu Catalysts. Issue 1 (16th October 2020) - Xu, Chaochen; Zhi, Xing; Vasileff, Anthony; Wang, Dan; Jin, Bo; Jiao, Yan; Zheng, Yao; Qiao, Shi-Zhang
Abstract : Cu‐based electrocatalysts with high catalytic selectivity for the CO2 reduction reaction present a significant technological challenge. Herein, a catalyst comprised of Cu single atoms in a nitrogen‐doped graphene matrix (Cu–N4 –NG) is developed for highly selective electrocatalytic reduction of CO2 to CO. The single‐atom structure and coordination environment of Cu–N4 –NG are identified by synchrotron‐based characterization. Compared to a conventional bulk Cu catalyst, Cu–N4 –NG achieves a Faradaic efficiency of 80.6% toward CO under a moderate applied potential of −1.0 V versus reversible hydrogen electrode (RHE). Kinetic experiments show that 1) the Cu–N4 moiety favors the CO2 activation step and 2) the moiety‐anchoring graphene facilitates water dissociation, which supplies protons for CO2 reduction. Moreover, density functional theory (DFT) calculations reveal that CO2 reduction is less hindered thermodynamically on Cu–N4 –NG compared to the competing hydrogen evolution reaction (HER) due to their limiting potential differences. Therefore, the highest CO selectivity is observed on Cu–N4 –NG over the bulk Cu catalyst due to more favorable kinetics and thermodynamics. Abstract : Single‐atom Cu embedded in N‐doped graphene (Cu–N4 –NG) is developed for CO2 electroreduction. The experimental results show that the presence of Cu–N4 structure promotes CO2 activation and H2 O dissociation, indicating the CO2 reduction process is kinetically favored on Cu–N4 –NG. The computational investigation indicates that CO2 reduction to CO is a less thermodynamic barrier than hydrogen evolution.